Contribution of Mental Strength to Academic Stress in High School Students - Nabila Rachman (International Conference on Psychology and Education (ICPE), 2023)
In the learning process in high school, students have the potential to experience stress due to task demands and their inability to complete learning tasks. Stress in the learning process is called academic stress. Various causes of academic stress include assignment demands that are considered too heavy, low test scores, a large number of assignments, and the surrounding environment. In other words, high school students need mental toughness in studying. The aim of this research is to reveal the influence of mental toughness on academic stress in high school students. This research is quantitative research. The subjects in this study were 65 class XI high school students in City 'X" who were selected using accidental techniques. The instruments used in this research were the mental toughness scale and the academic stress scale. The data analysis technique in this research uses linear correlation. The results show that p is 0.000 and the regression coefficient is -0.761 and the R2 value is 0.579, meaning that the influence of mental toughness on academic stress is 57.9%. This shows that there is an influence of mental toughness on academic stress in high school students in City "X". This research has implications for future researchers to uncover other factors that influence academic stress in high school students.